Elementary and Intermediate Algebra: Concepts & Applications (6th Edition)

Published by Pearson
ISBN 10: 0-32184-874-8
ISBN 13: 978-0-32184-874-1

Chapter 7 - Functions and Graphs - 7.4 The Algebra of Functions - 7.4 Exercise Set - Page 476: 35



Work Step by Step

RECALL: $(f-g)(x) = f(x)-g(x)$ Using the formula above gives: $(r-t)(x) \\= r(x)-t(x) \\=\dfrac{5}{x^2}-\dfrac{3}{2x}$ Make the expressions similar using their LCD $2x^2$ $=\dfrac{5(2)}{x^2(2)}-\dfrac{3(x)}{2x(x)} \\=\dfrac{10}{2x^2}-\dfrac{3x}{2x^2} \\=\dfrac{10-3x}{2x^2}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.